2016
DOI: 10.1017/s1092852916000717
|View full text |Cite
|
Sign up to set email alerts
|

Dysphoric mania, mixed states, and mania with mixed features specifier: are we mixing things up?

Abstract: Various terms have been used to describe mania when it is accompanied by depressive symptoms. In this article, we attempt to define and discuss 3 of these terms: dysphoric mania, mixed state, and mania with mixed features specifier. We conclude that whatever term is used, it is important to be aware that mania is more often unpleasant than pleasant, and that the unpleasantness is not limited to depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…23 This change broadened the conceptualization of mixed presentations in BD to a spectrum incorporating subthreshold symptoms of the opposite pole (Figure 4). 31 While the DSM-5 criteria were acknowledged to be a likely improvement in capturing the heterogeneity of mixed presentations, it is not without criticism. For example, the number of opposite pole symptoms (three) required to meet criteria for the specifier is not clearly based on empirical evidence.…”
Section: Conceptualization Of Mixed Presentationsmentioning
confidence: 99%
“…23 This change broadened the conceptualization of mixed presentations in BD to a spectrum incorporating subthreshold symptoms of the opposite pole (Figure 4). 31 While the DSM-5 criteria were acknowledged to be a likely improvement in capturing the heterogeneity of mixed presentations, it is not without criticism. For example, the number of opposite pole symptoms (three) required to meet criteria for the specifier is not clearly based on empirical evidence.…”
Section: Conceptualization Of Mixed Presentationsmentioning
confidence: 99%
“…The DSM-5 does not provide a clear rationale for not weighing certain depressive symptoms, such as weight loss or weight gain, decreased or increased appetite, and insomnia or hypersomnia for the establishment of a MFS in the context of mania (or hypomania) even though virtually every symptom of depression may co-occur in acute (hypo)manic episodes (18). Many patients with MDE and mixed features also present with manifestations of anxiety that are not captured by the MFS (18) as well as other clinical features, that is, aggressiveness that have been recently found to be a possible psychopathological indication of an underlying mixed state (19).…”
Section: Introductionmentioning
confidence: 99%
“…The DSM-5 does not provide a clear rationale for not weighing certain depressive symptoms, such as weight loss or weight gain, decreased or increased appetite, and insomnia or hypersomnia for the establishment of a MFS in the context of mania (or hypomania) even though virtually every symptom of depression may co-occur in acute (hypo)manic episodes (18). Many patients with MDE and mixed features also present with manifestations of anxiety that are not captured by the MFS (18) as well as other clinical features, that is, aggressiveness that have been recently found to be a possible psychopathological indication of an underlying mixed state (19). A recent study identified that a four-or five-symptom cluster composed by the DSM-5 MFS symptoms racing thoughts, increased talkativeness and decreased need for sleep and by the two non-specific symptoms distractibility and irritability, was shown at baseline in a placebo-controlled trial involving patients with MDD with mixed features (20).…”
Section: Introductionmentioning
confidence: 99%
“…The term bipolar disorder is a misnomer as manic and depressive symptoms often co-occur, perhaps in an infinite number of combinations. [1][2][3] Often called mixed states, the Diagnostic and Statistical Manual, 5th Edition (DSM-5) 4 recognizes two broad types of these combinations: (1) mania or hypomania (hypo/mania) with depressive symptoms (called hypo/mania with mixed features or mixed hypo/mania) and (2) depression with subsyndromal hypo/manic symptoms (called depression with mixed features or mixed depression). While both types of mixed states have been recognized since ancient times, 1 modern research has given far more attention to the diagnosis and treatment of mixed mania than to mixed depression.…”
Section: Introductionmentioning
confidence: 99%
“…A related concern is that the DSM-5 mixed features specifier is a categorical nosology while mixed states might better be conceptualized with dimensional models. 3,17 Thus, rather than specifying which and how many hypo/manic symptoms must occur in a depressive syndrome to define mixed depression, a certain level of subthreshold manic symptomatology, perhaps determined with a mania rating scale, including those that assesses specific as well as nonspecific manic symptoms, might be more appropriate. Indeed, trying to differentiate between mixed depressive vs mixed hypo/ manic states may sometimes be like differentiating between a particle and wave-it cannot be done with careful clinical observation, but may require assessment of response to an intervention (ie, administration of an antidepressant to see if symptoms improve, worsen, or stay the same).…”
Section: Introductionmentioning
confidence: 99%